Phyto‐fabrication, purification, characterisation, optimisation, and biological competence of nano‐silver. Issue 1 (2nd February 2021) - Ahmad, Bashir; Shireen, Farah; Rauf, Abdur; Shariati, Mohammad Ali; Bashir, Shumaila; Patel, Seema; Khan, Ajmal; Rebezov, Maksim; Khan, Muhammad Usman; Mubarak, Mohammad S.; Zhang, Haiyuan
Abstract: Published studies indicate that virtually any kind of botanical material can be exploited to make biocompatible, safe, and cost‐effective silver nanoparticles. This hypothesis is supported by the fact that plants possess active bio‐ingredients that function as powerful reducing and coating agents for Ag+. In this respect, a phytomediation method provides favourable monodisperse, crystalline, and spherical particles that can be easily purified by ultra‐centrifugation. However, the characteristics of the particles depend on the reaction conditions. Optimal reaction conditions observed in different experiments were 70–95 °C and pH 5.5–8.0. Green silver nanoparticles (AgNPs) have remarkable physical, chemical, optical, and biological properties. Research findings revealed the versatility of silver particles, ranging from exploitation in topical antimicrobial ointments to in vivo prosthetic/organ implants. Advances in research on biogenic silver nanoparticles have led to the development of sophisticated optical and electronic materials with improved efficiency in a compact configuration. So far, eco‐toxicity of these nanoparticles is a big challenge, and no reliable method to improve the toxicity has been reported. Therefore, there is a need for reliable models to evaluate the effect of these nanoparticles on living organisms.